Tăng cường độ phân giải trong phép chuyển trường xuống của các dữ liệu trường thế - Liệt, Đặng Văn; toàn, Lương Phước; Phương, Bùi Thị Ánh (Vietnam Journal of Earth Sciences, 2012)
summaryIntensified resolution of downward continuation of potential field dataPotential field data usually contain noises and in the downward continuation these noises with high frequency are amplified strongly that mask all useful information of the original data. Consequently, thedownward continuation maps are difficult to be interpreted. In this paper, we propose using a lineweight function (LWF) to eliminate the noises ofdownward continuation data. The method was applied on a gravity model, a magnetic profile and a gravity map. The results showed that this method can be used effectively to interpret local anomalies in filtered downward continuation data.